Global Perspectives on Democracy and Public Stadium Finance. Issue 4 (1st October 2020) - Kellison, Timothy; Sam, Michael P.; Hong, Sungil; Swart, Kamilla; Mondello, Michael J.
Abstract: Arenas, ballparks, and stadiums built for professional sports teams or mega-events all around the world often come with large public costs. In democratic states, citizens are assumed to have a role in public policymaking, but previous research suggests the strength of this role can vary case-to-case. To examine the incidence of public stadium finance and public participation across the geopolitical landscape, a collective case study was employed and organized into regime type (i.e., full democracies, flawed democracies, hybrid regimes, authoritarian regimes). The results of the study show clear contrasts in the financing mechanisms within and between regime types. Additionally, each case-study grouping contained examples of citizen-led public participation, though the efficacy of these democratic actions is questionable. This review complements the growing literature on public policy and stadium finance by assessing public engagement in current stadium-subsidy debates around the world.